Measurement of multiple mechanical properties for polymer composites using digital image correlation at elevated temperatures. (15th January 2021) - Hao, Ziqing; Ji, Xiaohui; Deng, Linlin; Ke, Hongjun; Liu, Liu
Abstract: This work presents a cost-effective experimental method for measuring multiple mechanical properties for carbon fiber reinforced modified epoxy matrix composites using the digital image correlation method at elevated temperatures. The method is based on combining a calculated stress distribution and a surface full-field strain measurement in a custom short-beam shear specimen. As the in-plane shear strain exceeds 0.01, all unidirectional SBS specimens exhibited highly nonlinear shear stress-strain behavior. Shear delamination failure occurred at elevated temperatures up to 150 o C. Axial elastic modulus and in-plane shear modulus were determined from 2-mm-wide gage regions mid-way between the loading nose and lower support in a single experiment using the closed-form approximation and finite-element-model-updating method. The average axial moduli determined using two different methods are highly consistent. The variation of multiple mechanical properties for the composite material with the temperature rising to 150 o C has been obtained simultaneously. The experimental results demonstrate that the axial elastic modulus decreased by only 5.2% at 100 o C and 7.8% at 150 o C, respectively. However, the in-plane shear modulus decreased by 20.8% at 150 o C. It indicates that the degradation of the in-plane shear behavior is sensitive to temperature rising since it is dominated by the matrix, which is sensitive to the glass transition temperature T g of epoxy resin. Graphical abstract: Unlabelled Image Highlights: An experimental method to determine multiple mechanical properties of composites at elevated temperatures is proposed. Both the closed-form approximation and finite-element-model-updating method can be used at elevated temperatures. The variation of multiple mechanical properties for composites with temperature rising has been obtained simultaneously. Degradation of the axial elastic modulus is insensitive to temperatures, and the shear modulus decreased by 20.8% at 150°C.